Penegakan Hukum dalam Tindak Pidana Pencurian Kendaraan Bermotor dalam Perspektif Kriminologi di Wilayah Hukum Polresta Sidoarjo - Dimas Putra Ardianto; Bangun Patrianto (Fakultas Hukum Universitas Bhayangkara Surabaya, 2025)
Motorcycle theft is one of the most persistent crimes in Indonesia, including within the jurisdiction of the Sidoarjo Regional Police. This study aims to analyze the law enforcement process regarding motor vehicle theft and identify the underlying criminological factors. The study uses an empirical legal approach, collecting data through in-depth interviews with criminal investigators from the Sidoarjo Regional Police and field observations. These are supported by relevant laws and legal literature. The results indicate that law enforcement carries out investigations and inquiries based on Articles 362, 363, and 365 of the Criminal Code (KUHP). The main obstacles are the lack of initial evidence and limited CCTV coverage. From a criminological perspective, internal factors, such as unstable economic conditions and perpetrators' low educational levels, along with external factors, including the influence of social circles, organized networks of receivers, and situational vulnerabilities, serve as the dominant triggers for this crime. The Sidoarjo Regional Police have implemented preventive measures, such as patrols, coordination with neighborhood watch groups, and community outreach, to reduce motorcycle theft.